2018
DOI: 10.18632/aging.101419
|View full text |Cite
|
Sign up to set email alerts
|

AVE0991, a nonpeptide analogue of Ang-(1-7), attenuates aging-related neuroinflammation

Abstract: During the aging process, chronic neuroinflammation induced by microglia is detrimental for the brain and contributes to the etiology of several aging-related neurodegenerative diseases such as Alzheimer's disease and Parkinson's disease. As a newly identified axis of renin-angiotensin system, ACE2/Ang-(1-7)/MAS1 axis plays a crucial role in modulating inflammatory responses under various pathological conditions. However, its relationship with aging-related neuroinflammation is less studied so far. In this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 43 publications
2
22
0
Order By: Relevance
“…The top three ranked multidimensional proteins that could represent effective age-related disease interdiction targets were, arginine vasopressin receptor 1B (AVPR1B), MAS1 proto-oncogene, GPCR (MAS1) and RLN3, the cognate ligand for the RXFP3 (Figure 11C). It is interesting to note that the MAS1 [196] and arginine vasopressin receptors [197] have recently been implicated in age-related disorder amelioration. In this context, using an unbiased multidimensional approach it is tantalizing to anticipate that therapeutic modulation of the RXFP3 may also hold significant promise for the attenuation of multiple age-related diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The top three ranked multidimensional proteins that could represent effective age-related disease interdiction targets were, arginine vasopressin receptor 1B (AVPR1B), MAS1 proto-oncogene, GPCR (MAS1) and RLN3, the cognate ligand for the RXFP3 (Figure 11C). It is interesting to note that the MAS1 [196] and arginine vasopressin receptors [197] have recently been implicated in age-related disorder amelioration. In this context, using an unbiased multidimensional approach it is tantalizing to anticipate that therapeutic modulation of the RXFP3 may also hold significant promise for the attenuation of multiple age-related diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it was of great signi cance to study the role of Mas receptor in acute allergic airway in ammation. Considering that Ang-(1-7) exerted a short duration of biological effect in vivo for rapid degradation by ACE which was rich in lung [34], we employed AVE0991, a synthetic non-peptide agonist of Mas receptor, in subsequent experiments to further evaluate the role of Mas receptor in acute allergic airway in ammation. Different from studies in MG Rodrigue-Machado [17,18], we further performed the immuno uorescence double staining to co-localize Mas receptor with EpCAM, which con rmed that Mas receptor mainly acted on airway epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, AVE0991 was found to attenuate the neuroinflammation related to the ageing process through the suppression of the microglial-mediated inflammatory response [127]. In addition to this, the intranasal administration of ACE0991 in the animal study reduced oxidative stress and neural apoptosis, and improved neurobehavioral scores in brain injury after subarachnoid hemorrhage.…”
Section: New Perspectives In Targeting Ras Mas Atr2 and Atr4 Recmentioning
confidence: 99%